PARTISIPASI MASYARAKAT TERHADAP PROGRAM RUMAH PANGAN LESTARI - Cisyara, Sinta Naila; Novyantari, Zahrani Tri; Khotimah, Iin Husnul; Novitasari, Nastiti (Jurnal Pengabdian Masyarakat Indonesia, 2024)
Sukahurip Village, especially Cikujangbeet Hamlet, is one of the hamlets whose area is larger in forests and plantations compared to the community's residential area. For their livelihood, of course the majority are rice and vegetable farmers. In this year's agricultural unit program we are focusing on empowering women in Cikujangbeet Hamlet, namely by strengthening the Mekar Binangkit Women's Farming Group (KWT). One of the activities of the Mekar Binangkit Women's Farmers Group (KWT) is implementing the Sustainable Food House program, however this program is not sustainable. It would be a shame if the program was not continued because we feel that the Women Farmers Group (KWT) has great potential in developing the Sustainable Food House (RPL) program, especially for those who already have knowledge from previous experience. The aim of continuing the Sustainable Food House program is to utilize the land around the house to support the sustainability of family food security through organic planting of vegetables, fruit and other food crops.